Analysis of Erythrocyte C4d to Complement Receptor 1 Ratio: Use in Distinguishing between Infection and Flare-Up in Febrile Patients with Systemic Lupus Erythematosus. (26th July 2015) - Chen, Chen-Hung; Tai, Shun-Ban; Chen, Hsiang-Cheng; Yang, Deng-Ho; Peng, Ming-Yieh; Lin, Yuh-Feng
Abstract : Objective. Fever in systemic lupus erythematosus (SLE) can be caused by infection or flare-up of the disease. This study aimed to determine whether the ratio of the level of erythrocyte-bound C4d to that of complement receptor 1 (C4d/CR1) can serve as a useful biomarker in the differentiation between infection and flare-up in febrile SLE patients. Methods. We enrolled febrile SLE patients and determined the ratio on the day of admission. The patients were divided into 2 groups according to the subsequent clinical course. Results. Among the febrile SLE patients, those with flare-up had higher ratios and lower C-reactive protein (CRP) levels than those with infection. Cut-off values of <1.2447 and >4.67 for C4d/CR1 ratio and CRP, respectively, were 40.91% sensitive and 100.0% specific for the presence of infection in febrile SLE patients; similarly, cut-off values of >1.2447 and <2.2, respectively, were 80% sensitive and 100% specific for the absence of infection in febrile SLE patients. Conclusion. The C4d/CR1 ratio is a simple and quickly determinable biomarker that enables the differentiation between infection and flare-up in febrile SLE patients at initial evaluation. Further, when combined with the CRP level, it is useful to evaluate disease activity in SLE patients with infection.